The Financial Crisis Implications for Research and Teaching - Azarmi, Ted; Amann, Wolfgang (Springer International Publishing : Imprint: Springer, 2016)
This book brings together a good mix of academics and practitioners for a discussion that focuses on how to change financial practice and the academic field of finance in order to understand the current financial crisis and deal with future turbulent financial times. The volume is based on contributions by prominent academics and practitioners from Europe, Asia and the USA. The book contains several essays, most prominently by Maurizio Murgia, an internationally renowned European corporate finance scholar, and Robert E. Krainer, a senior professor with banking and business cycles research interest from University of Wisconsin-Madison. This book also deals with pedagogical, empirical and theoretical considerations in light of the crisis. .